Mandatory adoption of IFRS and earnings management in emerging countries: the role of national culture - Junior, D. B. C. V.; Ohlson, M. P.; Lourenço, I. M. E. C.; De Lima, G. A. S. F. (American Accounting Association Annual Meeting, 2018)
This study examines whether the characteristics of national culture, as proposed by Hofstede, Hofstede and Minkov (2010), are moderating factors on the potential impact of IFRS mandatory adoption on the quality of accounting information in emerging countries. The quality of information was measured through earnings management by accruals, based on the model of Jones (1991) modified by Dechow, Sloan and Sweeney (1995). Through a sample of 2,458 companies from 13 countries, totaling 18,163 firm-year observations, we identified that the dimensions of individualism, masculinity, aversion to uncertainty, long-term orientation and indulgence moderates the impact of IFRS adoption on earnings management levels in emerging countries. It was not possible to identify evidence that the power distance dimension exerts such influence. Overall, this study adds to the literature on the effect of cultural factors on accounting quality.